Perlindungan Konsumen Atas Produk Pangan Berlabel Halal: Tinjauan Yuridis - Aksamawanti Aksamawanti (Syariati: Jurnal Studi Al-Qur'an dan Hukum, 2015)
Nowdays, muslim in the world are starting to realize the\at the development of science and technology has led to the problem of determination halal food and beverage products become simple. Demands clarity halal staus of a food product has become part of a global issue. It is not because of the Islmaic view of the halal statuse issue has broad implications covering various aspect of life. Thus, eating halal food products become sosial problems in the community as well as a responsibility of the state and the rights of citizens guaranteed by the Constitution of 1945 on the basis of the same idea, namely the insurance of halal products. The purpose of this stydy was to determine whether the regulations set by the goverment, al ready provide proctection to consumers to consume halal food products? In this study used normative juridical method with descriptive nature. Based on the research result and in the accordance with the issues that have been outlined, the regulations set bay goverment is still pasrtial, sectoral and overlap, so it didi not provide consumer protection on food labeled as halal.